TEACHING PRODUCTIVE SKILL THROUGH VARK - Rijal, Samsi; arifah, nurdiana (WACANA DIDAKTIKA, 2017)
Teaching English as foreign language to Indonesia learners is rather difficult. It can be seen from most of learners who graduated from university, they cannot use English as their language for communication; written or spoken communication. In addition, Most of teachers use traditional method or strategy that focuses on teacher or teacher center. So, students are not only active in joining the class but also feel bored. Dealing with this problem, the teachers must change their teaching from teacher center to learner center. Furthermore, teaching productive skill; writing and speaking, the teacher must use the suitable strategy to achieve goal of teaching and learning process. VARK (Visual, Auditory, Read/Write, and Kinesthetic) which is developed by Neil Fleming in 1987 is one of the strategies which can be used to teach productive skill, because it invites learners more active in joining the class. It also helps learners in understanding the materials easily.